State-of-the-Art in Orthodontics and Gnathology - Minervini, Giuseppe; d'Apuzzo, Fabrizia; Grassia, Vincenzo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The objective of this reprint is to present the main evidence-based data on new developments and knowledge in diagnostic and treatment technologies in the orofacial field used in both children and adults. The published content has been met with great success in interdisciplinary fields, stimulating international authors to submit their original articles, reviews, or case reports based on various aspects of orthodontics as well as on the diagnosis and management of temporomandibular disorders and orofacial pain. Among the current highly debated topics, this reprint focuses on multiple disciplines as follows: gingival recessions and periodontal status after orthodontic treatment; a rare case of impacted central incisors; predictors of analgesic consumption in orthodontic patients; a systematic review about different dentoskeletal class III treatment approaches; evaluation of upper airway volumes; and cephalometric values in JIA patients.